Towards high-sensitive built-in current sensors enabling detection of radiation-induced soft errors. (November 2017) - de Oliveira Rocha, Raphael; Sill Torres, Frank; Bastos, Rodrigo Possamai
Abstract: Soft error resilience is an increasingly important requirement of integrated circuits realized in CMOS nanometer technologies. Among the several approaches, Bulk Built-in Current Sensors (BBICS) offer a promising solution able to detect particle strikes immediately after its occurrence. Principal challenges for its wide application in common designs are area costs and robustness, both directly related to the sensor's sensitivity. Following this requirement, this work presents strategies enabling the design of high-sensitive BBICS. In detail, we are proposing three approaches based on gate voltage control, body biasing, and stack forcing that can be integrated in all state-of-the-art BBICS architectures. In order to verify the feasibility of this approaches, the proposed techniques have been integrated in a modular BBICS realized in a commercial 65 nm technology. Simulation results indicate an increase of the detection sensitivity by up to factor 6, leading to 17% area overhead, response times around 1 ns, a negligible power penalty, and high robustness against wide variations of temperature and process parameters. Highlights: Strategies for considerable improvements of state-of-the-art BBICS are presented. These sensors enable fast detection of radiation induced soft errors Results indicate improvements of up to factor 6. Compared to related techniques, BBICS stand out by avoidance of a delay penalty.